2007
DOI: 10.1074/jbc.m611599200
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Apoptotic Signaling Pathways Probed and Intervened by Synthetically and Modularly Modified (SMM) Chemokines

Abstract: As the main coreceptors for human immunodeficiency virus type 1 (HIV-1) entry, CXCR4 and CCR5 play important roles in HIV-associated dementia (HAD). HIV-1 glycoprotein gp120 contributes to HAD by causing neuronal damage and death, either directly by triggering apoptotic pathways or indirectly by stimulating glial cells to release neurotoxins. Here, to understand the mechanism of CXCR4 or CCR5 signaling in neuronal apoptosis associated with HAD, we have applied synthetically and modularly modified (SMM)-chemoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…In any case, ample published evidence supports a crucial role for macrophages and microglia in HIV-1 and gp120-induced neurotoxicity (33,48,5660). The implication of microglia in gp120-induced neuronal injury in vivo is also in line with our finding of increased numbers of this cell type in cerebral cortex and hippocampus of gp120 mice.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, ample published evidence supports a crucial role for macrophages and microglia in HIV-1 and gp120-induced neurotoxicity (33,48,5660). The implication of microglia in gp120-induced neuronal injury in vivo is also in line with our finding of increased numbers of this cell type in cerebral cortex and hippocampus of gp120 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid-β-induced activation of p38 MAPK resulted in upregulation of pro-inflammatory cytokines TNFα, inducible NO synthase (iNOS), and IL-1β, and subsequent neuronal death (Delgado et al 2008). Our and other groups have shown that inhibition of p38 MAPK activity in vitro with pharmacological inhibitor SB203580 or dominant negative p38αAF (TGY substituted with AGF) prevented neuronal apoptosis induced by HIV-1 gp120 or glutamate (Kaul and Lipton 1999; Singh et al 2005; Kaul et al 2007; Choi et al 2007; Chaparro-Huerta et al 2008; Fig. 1b).…”
Section: Involvement Of P38 Mapk In Hiv Infection and Development Of mentioning
confidence: 71%
“…However, we and others have found an essential role for p38 MAPK in the induction of neuronal injury and apoptotic death by HIV-1 gp120, Tat and the intact virus (Kaul and Lipton 1999; Kaul et al 2007; Choi et al 2007; Medders et al 2010; Singh et al 2005; Sui et al 2006; Eggert et al 2010; Fig. 1).…”
Section: Involvement Of P38 Mapk In Hiv Infection and Development Of mentioning
confidence: 74%
See 1 more Smart Citation
“…CXCR4 signaling may be pro-apoptotic through activation of E2F1 [27] or anti-apoptotic through activation of Akt [42]. Although the role of SDF-1 signaling in epilepsy is unresolved, we speculate that it could be important therapeutically using synthetically modified CXCR4 and CCR5 ligands modulating neuronal survival rather than apoptosis [43]…”
Section: Discussionmentioning
confidence: 99%